The Influence Of Celebrity Endorsement, Brand Image And Online Customer Reviews On Purchasing Decisions For Erigo Products Online (Study On All Erigo Product Users In Indonesia) - Ikfina Rizki; Sukaris Sukaris (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of Celebrity Endorsement, Brand Image, and Online Customer Reviews on purchasing decisions for Erigo products online. The research employs a quantitative method with a causal approach, involving 102 respondents selected through the Incidental Sampling method. Data analysis was conducted using multiple linear regression to examine the effect of each independent variable on the dependent variable. The results indicate that all three variables—Celebrity Endorsement, Brand Image, and Online Customer Review—have a positive and significant effect on purchasing decisions. Collectively, the independent variables explain 47.3% of the variation in purchasing decisions, while the remaining percentage is influenced by other factors outside this study. These findings contribute theoretically to the development of digital marketing knowledge and provide practical implications for advancing local product marketing strategies.